The Responsibility Of A Notary For Negligence In Handling Business Licensing Through Oss-Rba - Sya’ban Tiar, Risvan; Sesung, Rusdianto (IHSA Institute, 2025)
Based on the results of the study, it can be concluded: First: With the granting of a power of attorney by a business actor to a notary, it clearly creates a legal relationship in which the notary acts on behalf of all the legal interests of the business actor, gives authority and responsibility, as well as gives birth to rights and obligations that arise between the two parties. A notary who carries out the business licensing process through the OSS system can be held accountable based on a power of attorney agreement that creates rights and obligations for the principal and the attorney. The responsibilities that arise are civil responsibility and moral responsibility related to the notary's code of ethics. Second, for the occurrence of typographical errors in the minutes of the deed, these errors can be corrected by making changes or by replacing, adding, crossing out, or inserting words. These changes may only be made to the contents of the deed, not at the beginning and end of the deed. The change is valid if it is initialed or given other validation marks by the signer, witness, and notary. The notary's responsibility for the occurrence of typographical errors in the minutes of the deed that have been issued copies is to directly make changes to the draft of the deed by reprinting it if the facing is still available and there is office equipment to support it. However, if the appearers are no longer present before the notary, the notary must contact the appearers again to make improvements to the deed (not changes)